Hubungan Antara Tingkat Pengetahuan, Sikap, Dan Tindakan Ibu Dengan Cakupan ASI Eksklusif Pada Bayi Umur 0-6 Bulan Di Kelurahan Tandurusa Kota Bitung - Puji Amartiwi; Agusteivie A. J. Telew; Alva Supit (Yayasan Syalom Cipta Sumikolah, 2024)
The exclusive breast milk (MMA) is an important step in ensuring the optimal health and development of the baby. The study aims to analyze the relationship between the level of knowledge and mother's attitude towards exclusive breastfeeding coverage in Tandurusa Kelurahan, Bitung City. The study used a cross-sectional design with a total of 34 samples of mothers who had a baby aged 0-6 months. Data is collected through questionnaires that have been tested for validity and reliability. The results of the study showed that there was no significant relationship between the level of knowledge of mothers with exclusive breastfeeding coverage (p=0.42) and the mother's attitude to exclusive milk (p =0.63). Based on the results, it is recommended to undertake further